Authentication of Rusa timorensis DNA Using Sequencing Assay with Modified Extraction Method - Ishak, Nooratiny; Mat Lazim, Azwan (Halalsphere, 2022)
A technique to isolate DNA from deer meat was established to authenticate the deer species and was successfully extracted from deer meat. The method was based on the Epicentre MasterPureTM Complete DNA and RNA Purification Kit extraction kit with slight modification by increasing the volume of Proteinase K and RNase from 5 µL to 20 µL each. The recovery of deer DNA was then analysed by Polymerase Chain Reaction using cytochrome b gene oligonucleotide primers for the deer family, which targeted the mitochondrial DNA. The increasing volume of Proteinase K and RNase resulted in clean DNA and no smearing after performing Polymerase Chain Reaction. Furthermore, the amplified DNA product was extended to sequence assay to authenticate deer species above 95% maximum identification. The result showed that the increasing volume of Proteinase K and RNase offered a high yield of DNA recovery, which provided more than 100 ng per μL and was useful in validating animal-based sources, especially in deer products.